Altered redox status in the blood of psoriatic patients: involvement of NADPH oxidase and role of anti-TNF-α therapy. (May 2013) - Barygina, V.V.; Becatti, M.; Soldi, G.; Prignano, F.; Lotti, T.; Nassi, P.; Wright, D.; Taddei, N.; Fiorillo, C.
Abstract : Background: Psoriasis is a chronic hyperproliferative inflammatory skin disease, characterized by a generalized redox imbalance. Anti-tumor necrosis factor (TNF)-α therapy is widely used for the treatment of this disease, but its effect on blood redox status hasn't been explored. Objective: To investigate the effects of anti-TNF-α therapy on blood redox status in psoriatic patients. Methods: Twenty-nine psoriatic patients (PSO) were divided into two groups: one remained untreated (NRT) and to another the anti-TNF-α therapy was prescribed (TR). The levels of main oxidative stress markers and total antioxidant capacity (TAC) in plasma, levels of total reactive oxygen species (ROS) production, lipoperoxidation, TAC, glutathione content, and activity of NADPH oxidase in white blood cells (WBC) were evaluated in PSO, in NTR and TR after 6 months of the study. Results: Plasma levels of malondialdehyde (MDA) and protein carbonyl content (PCO), ROS production, lipoperoxidation, and glutathione content in WBC were increased, while TAC in both plasma and WBC was decreased in PSO with respect to controls. In the plasma of TR, levels of MDA and PCO were significantly lower with respect to PSO and NTR. The activity of NADPH oxidase was significantly increased in WBC of PSO and NTR but not in TR versus controls. Discussion: Our results represent novel data about the redox status of WBC in psoriatic patients. A significant redox-balancing effect of anti-TNF-α therapy, probably associated with the normalization of NADPH oxidase activity in WBC, was demonstrated.